Klebsiella pneumoniae Liver Abscess and Metastatic Endophthalmitis. (31st December 2015) - Wells, Jason T.; Lewis, Catherine R.; Danner, Omar K.; Wilson, Kenneth L.; Matthews, L. Ray
Introduction. Klebsiella pneumoniae is a well-known cause of liver abscess. Higher rates of liver abscess associated with Klebsiella pneumoniae are seen in Taiwan. Metastatic endophthalmitis is a common complication associated with a poor prognosis despite aggressive therapy. Case Report . We report a case of a 67-year-old Korean female with Klebsiella pneumoniae liver abscess. The patient developed metastatic endophthalmitis and ultimately succumbed to her disease despite aggressive medical and surgical treatment. Conclusion . Dissemination of Klebsiella pneumoniae is associated with significant morbidity and mortality. Liver abscesses preferably should be treated with percutaneous drainage, but surgical treatment is needed in some cases. Metastatic spread to the eye is a common complication that must be treated aggressively with intravenous antibiotics and surgical intervention if necessary.